Secure patient-therapist attachment following therapy for personality disorder in a forensic mental health setting - Willmot, Phil (The journal of forensic psychiatry & psychology, 2024)
Therapy for personality disorder can be understood as a process of enhancing attachment security. This study tests the theory that individuals in a secure forensic mental health setting with a diagnosis of personality disorder who have undertaken psychological therapy will report secure patterns of attachment in their relationship with their therapist. It uses a novel pattern matching approach that assesses the behavioural, cognitive and affective markers of attachment security in a group of patients undergoing therapy. Eight behavioural, cognitive and affective characteristics of secure attachment were identified. Ten patients completed a semi-structured interview about their experiences in therapy and key relationships, and their responses were reviewed for evidence of these eight characteristics. Nine out of ten participants were judged to have demonstrated a pattern of six or more of the eight characteristics of secure attachment. This study supports the theory that treatment for this group of patients works by developing patient-therapist attachments. A focus on attachment issues should, therefore, be a core aspect of therapy.